PERKEMBANGAN SENI KRIYA DI TENGAH PERUBAHAN MASYARAKAT - Sunarya, I Ketut (Imaji: Jurnal Seni dan Pendidikan Seni, 2015)
As human creation, fine art is a human or cultural fact as well as a semiotic fact. A fine art has a specific existence that distinguishes it from other human facts, that is an existence feature inseparable from the balance consideration between reason and feeling. Therefore, despite an artist’ freedom in actualizing and appreciating what he wants to express, he needs to hold the basic principle of fine art, namely its closeness to human life. The basic concept of the art is as a starting point and the artist’ mirror to reflect his duty to keep its potential of typical areas and to open new art horizon in creating a new classification system. This is a real step expected to determine the art’s position and bargaining value in this rapid growing era. Key words: fine art, and social changes